Ultra-fast generic LC-MS/MS method for high-throughput quantification in drug discovery - Kim, S.-H.; Yoo, H.H.; Cha, E.-J.; Jeong, E.S.; Kim, H.J.; Kim, D.H.; Lee, J. (2013)
An ultra-fast generic LC-MS/MS method was developed for high-throughput quantification of discovery pharmacokinetic (PK) samples and its reliability was verified. The method involves a simple protein precipitation for sample preparation and the analysis by ultra-fast generic LC-MS/MS with the ballistic gradient program and selected reaction monitoring (SRM) mode. Approximately 290 new chemical entities (NCEs) (over 10,000 samples) from 5 therapeutic programs were analyzed. The calibration curves showed good linearity in the concentration range of 1, 2 or 5 to 2000 ng/mL. No significant ion suppression was observed in the elution region of all the NCEs. When approximately 300 plasma samples were continuously analyzed, the peak area of internal standard was constant and reproducible. In the repeated analysis of samples, the plasma concentrations and the area under the curve (AUC) were consistent with the results from the first analysis. These results showed that the present ultra-fast generic LC-MS/MS method is reliable in terms of selectivity, sensitivity, and reproducibility and could be useful for high-throughput quantification and other bioanalysis in drug discovery.